Transformasi Pola Konsumsi Masyarakat Indonesia di Era Digital: Implikasi terhadap Keberlanjutan Ekonomi dalam Perspektif SDG 12 - salim, dhea; Hikmalia Safitri; Fazar Nuriansyah; Lazuardi Imani Hakam (Jurnal Ekonomis, 2025)
Digital transformation has significantly changed Indonesians' consumption patterns, driven by the development of e-commerce and the digitization of financial services. Easy access to goods and services through online platforms increases consumption, but also poses challenges to economic sustainability, such as resource exploitation, increased waste, and the risk of impulsive consumption. This research aims to analyze how changes in consumption patterns in the digital era can be directed towards more sustainable practices in accordance with Sustainable Development Goals (SDGs) 12. The research method used is Systematic Literature Review (SLR) with the PRISMA approach to screen and analyze literature related to digital consumption transformation and its impact on economic sustainability. The data was analyzed thematically to identify the driving factors of consumption change in the digital era. The results show that digitalization increases consumption efficiency, but also risks encouraging impulsive shopping patterns and increasing waste from e-commerce. On the other hand, digital technology has the potential to support sustainable consumption through innovations such as big data, artificial intelligence, and supply chain optimization. In conclusion, supportive regulations, increased digital literacy, and economic policies that balance consumption growth with sustainability principles are needed so that digitalization does not become a threat to economic and environmental stability.